LITERASI BUDAYA MELALUI CERPEN: STUDI KASUS INTEGRASI KEARIFAN LOKAL DALAM PEMBELAJARAN MENULIS DENGAN MODEL CTL DI SEKOLAH DASAR - Rahayuningsih; Jeffry Handhika; Dwi Rosita Sari (CV Edujavare Publishing, 2026)
Cultural literacy in elementary schools can be developed through writing activities that integrate local wisdom. This study aims to describe the process and outcomes of integrating Madiun's local wisdom in short story writing learning using the Contextual Teaching and Learning (CTL) model for sixth-grade students at SDN Ngranget, Madiun Regency. This research employs a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with teachers and students, and document analysis of learning plans and student work. Thematic data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the CTL model successfully facilitated students in exploring and constructing ideas based on direct experiences with local wisdom. Student engagement and motivation increased significantly, resulting in short stories that reflect local values such as mutual cooperation (gotong royong), environmental care, and socio-cultural traditions of Madiun. This study concludes that CTL is an effective pedagogical strategy for developing cultural literacy through contextual and meaningful writing learning.